Transformation of the aquaculture value-chain in Southern Bangladesh - Khondker, Murshed-E-Jahan; Ali, Hazrat (WorldFish, 2024)
The aquaculture sector in Bangladesh has grown rapidly over the past three decades, yet the organization and conduct within its value chain remain underexplored. This study addresses the gap through a "stacked survey" (November 2020–August 2022) involving 1,195 actors across five key nodes: hatcheries, feed traders, farms, wholesalers, and retailers in southern Bangladesh. Findings reveal significant growth in production volume and participation, with domestic fish comprising 84% of output and export-oriented crustaceans 16%. Disease outbreaks have driven shifts from shrimp to prawn and crustaceans to fish, intensifying production and increasing reliance on formulated feeds. Productivity averages 3,284 kg/ha, higher in fish-only farms. The value chain, predominantly family-operated, generates 490,000 full-time jobs with modest profit margins. These insights highlight a dynamic, competitive, and efficient sector, informing future interventions and policies.